CULTURAL UTILIZATION OF MANIPULATIVE TECHNOLOGIES (Proceedings of Southern Federal University. Philology, 2014)
The article makes an attempt to study manipulative strategies, carry out subsequent analysis of semantic techniques (logic tricks, plays with topic: paralipsis and actualization of irrelevant data, tropes) and syntactical methods (iteration and symmetry), and then observe what happens to the manipulative technique, after it has been disavowed. The paper is based on three aspects of language - semantics, syntax and pragmatics - taking into account that it is pragmatics that changes when manipulation becomes socially productive.Keywords: manipulation, persuasion, rhetoric, tropes, logical tricks, Topeka.Authors: Lobas P.P., Khasagerov G.G.